2004
DOI: 10.1210/jc.2003-031235
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Sensitivity Is Determined by a Specific Glucocorticoid Receptor Haplotype

Abstract: Differences in glucocorticoid (GC) sensitivity may underlie both common diseases (e.g. hypertension) and variability in response to treatment with GCs (e.g. asthma). We tested the potential involvement of the GC receptor (GR) gene in mediating GC sensitivity using haplotype analysis and a low-dose dexamethasone suppression test. Linkage disequilibrium across the GR gene was determined in 216 U.K. Caucasians, and 116 had a 0.25-mg overnight dexamethasone suppression test. Very strong linkage disequilibrium was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
116
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(133 citation statements)
references
References 37 publications
17
116
0
Order By: Relevance
“…SH30068). This batch of FBS was found to contain less than 9 nM cortisol as measured by RIA, as previously reported (Stevens et al 2004), giving a final calculated concentration in the cell-culture medium of less than 1 nM. The FBS was not heat inactivated (Anonymous 1996).…”
Section: Methodssupporting
confidence: 67%
“…SH30068). This batch of FBS was found to contain less than 9 nM cortisol as measured by RIA, as previously reported (Stevens et al 2004), giving a final calculated concentration in the cell-culture medium of less than 1 nM. The FBS was not heat inactivated (Anonymous 1996).…”
Section: Methodssupporting
confidence: 67%
“…Nevertheless, we did observe trends for each of the three analyzed GR variants, some of them apparently conflicting with the previously shown characteristics of the respective GR variants. Screening samples carrying the BclI variant, which, similar to N363S, is considered to increase GR sensitivity (17,18), revealed a trend towards higher 4-androstenedione concentrations, in contrast to lower steroid hormone concentrations (11-deoxycortisol and 21-deoxycortisol) in carriers of 363S. Linear regression analysis even revealed a statistical significance for the increase of 4-androstenedione levels in carriers of one or two BclI alleles, hereby suggesting the presence of an allele dose effect.…”
Section: Discussionmentioning
confidence: 91%
“…In several inflammatory diseases, variations in glucocorticoid sensitivity have been reported to be associated with SNPs in the GR gene [13,[28][29][30] . In this study we found no evidence of independent involvement of GR allelic variants (R23K and N363S) and CD phenotypic and clinical parameters, despite the reported correlations of the variants N363S with glucocorticoid hypersensitivity [13] and R23K with decreased response to dexamethasone [29] .…”
Section: Discussionmentioning
confidence: 99%